Accrual Based Earnings Management: The Case of Saudi Arabia - Alhassan , Ali (The Arab Journal of Administration, 2018)
This study analyzes the effectiveness of Modified Jones Model in detecting earnings management among the companies offerings that are listed between 2011 – 2015 in the Saudi Stock Exchange (SSE). Prior research documented that the Modified Jones model is effective in detecting earning management in mostly developed economies. Results of our study confirmed that Modified Jones model is effective in detecting earnings management in the context of Saudi Arabia. We employed the modified Jones model to detect earning management in context of the Saudi Stock Exchange (SSE) and found out that: Rabigh petrochemical industries, results showed that the administration did not practice earnings management during the years from 2012 -2015, while the results showed the practice of earnings management in the year 2011. Saudi Basic Industries Corporation (SABIC), results showed that the administration did not practice earnings management during the years from 2011 -2013, while the results showed the practice of earnings management in the years 2014 and 2015. National Industrialization Company, results showed that the administration do practice earnings management during the years from 2011 -2014, while the results showed the practice of earnings management in the year 2015. Sahara Petrochemical Company, results showed that the administration do practice earnings management during the years from 2011 -2014, while the results showed did not practice of earnings management in the years 2015 . Yanbu National Petrochemical Company (Yansab), results showed that the administration do practice earnings management during the years from 2011 -2013, while the results showed did not practice of earnings management in the years 2014 and 2015 . This study then attempted to extend the modified Jones model and found it to be very successful. Therefore it is concluded that the modified Jones model is effective in estimating the extent of earnings management practiced in the Saudi Stock Exchange (SSE) in petrochemical industries.